Pemenuhan Hak dan Perlindungan Penganut Agama Kepercayaan di Dusun Air Abik Bangka Belitung:Tinjauan dari Perspektif Hak Asasi Manusia - Sultan Sahala Pramuja; Robi Rendra Tribuana (CV Rewang Rencang, 2025)
This research aims to analyze the extent to which the fulfillment of rights and protection of religious believers in Dusun Air Abik, Bangka Belitung,based on a human rights perspective. The community of religious believers still faces social problems that affect the fulfillment of their basic rights. Based on socio-legal methods and empirical approaches,this study found that the fulfillment of the rights of religious believers LOM tribe has not been fully fulfilled.The local government must play an important role in encouraging the protection of rights through fair and equal policies. The conclusion shows that the government, especially the village government,must pay more attention to their rights that have not been fully fulfilled to ensure the fulfillment of equal human rights for all citizens.